THE METHOD OF CALCULATING THE ACOUSTIC FEATURES OF "RAIL - FOREIGN OBJECT" - Voitenko, V. P.; Osenin, Yu. I. (Science and Transport Progress, 2006)
A calculation technique is suggested for the system of the rail track and a foreign body on its surface. The procedure allows calculating a decrease of the intra-rail acoustic signal amplitude affected by the presence of a foreign body on the rail surface depending on the body substance density and the speed of acoustic wave propagation in the body substance.